Glutardialdehyde modified corn starch – urea formaldehyde resin as a binder for particleboard making - Mohd Hazim Mohamad Amini; Rokiah Hashim; Nurul Syuhada Sulaiman; Othman Sulaiman; Shaida Fariza Sulaiman; Faizah Abood; Fumio Kawamura; Razak Wahab; Mazlan Mohamed; Mohd Sukhairi Mat Rasat (2015)
The objective of the study was to characterize and to evaluate physical and mechanical properties of experimental particleboard panels made from rubberwood (Hevea brasiliensis) using modified starch-urea formaldehyde as binder. Panels were manufactured using 13% corn starch modified with glutardialdehyde with addition of 2 % urea formaldehyde resin and tested for their physical and mechanical properties. All of the particleboards satisfied the Japanese Industrial Standard which required 2000 N/mm2, 8.0 N/mm2 and 0.15 N/mm2 for modulus of elasticity, modulus of rupture and internal bonding strength, respectively. The mechanical properties were comparable to those made using 15 % urea formaldehyde resin with reduction of formaldehyde fume was over 50 %.